Yakutia National-Cultural Associations in Socio-Political History of Region in Late 20th - early 21st Centuries - S. A. Grigoryev (Научный диалог)
The history of creation and development of national-cultural associations of the peoples of Yakutia on the turn of 20th-21st centuries is described. It is noted that the preservation of the stability of ethnic relations in the multinational republic is the most important task of domestic policy carried out by local authorities. Information about the most important and most active public organizations representing different ethnic groups in the Republic of Sakha (Yakutia) is provided. The author discusses the Yakut national organizations “Sakha omuk” and “Sakha keskile,” played a significant role in the political development of Yakutia in 1990-ies. The article highlights the activities of associations of indigenous peoples of the North. The major public enterprises of the Russian population of the Republic and the Diaspora of various ethnic groups are described. It is shown that, despite the different scales and different degree of influence, national-cultural associations of the peoples of Yakutia played a significant role in the development of statehood of the Republic. The recognition of the sovereignty of the Republic of Sakha (Yakutia), as well as the preservation of interethnic peace and unity in it are the result of the active position of independent public-political organizations. It is noted that national-cultural communities and associations remain an important and stable part in the political processes in the Republic of Sakha (Yakutia).